2020
DOI: 10.3389/fimmu.2020.01585
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Epithelial Cells Promote IGF-1 Production by Alveolar Macrophages Through TGF-β to Suppress Endogenous Inflammatory Signals

Abstract: To maintain alveolar gas exchange, the alveolar surface has to limit unnecessary inflammatory responses. This involves crosstalk between alveolar epithelial cells (AECs) and alveolar macrophages (AMs) in response to damaging factors. We recently showed that insulin-like growth factor (IGF)-1 regulates the phagocytosis of AECs. AMs secrete IGF-1 into the bronchoalveolar lavage fluid (BALF) in response to inflammatory stimuli. However, whether AECs regulate the production of IGF-1 by AMs in response to inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This AM-derived IGF-1 attenuated the p38 mitogen-activated protein kinase inflammatory signal in AECs and promoted the phagocytosis of apoptotic cells by AECs. This two-way communication between AECs and AMs represents a well-tuned system for the regulation of the inflammatory response in alveoli ( Mu et al, 2020 ). Taken together, these studies provide biological evidence supporting that IGF-1 might be an important anti-inflammatory factor in the alveolar microenvironment and thus may contribute to improve COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This AM-derived IGF-1 attenuated the p38 mitogen-activated protein kinase inflammatory signal in AECs and promoted the phagocytosis of apoptotic cells by AECs. This two-way communication between AECs and AMs represents a well-tuned system for the regulation of the inflammatory response in alveoli ( Mu et al, 2020 ). Taken together, these studies provide biological evidence supporting that IGF-1 might be an important anti-inflammatory factor in the alveolar microenvironment and thus may contribute to improve COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IGF-1 is involved in regulating the biological responses of the immune system through phosphatidylinositol-3-kinases/protein kinase B (PI3K/AKT) and mitogen-activated protein kinase (MAPK) signaling pathways (Myers et al 1992 ). Various studies have proven the role of the IGF-1 signal transduction in lung development, as well as inflammatory diseases like ALI and Acute respiratory disease syndrome (ARDS), asthma, cancer, inflammation, and fibrosis (Stiles and D'Ercole 1990 ; Ahasic et al 2012 ; Mu et al 2020 ; Narasaraju et al 2006 ; He et al 2019 ; Li et al 2016 ). IGF-1 is also implicated in the regulation of inflammation in the immune system (DeBoer et al 2017 ; Heemskerk et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that crosstalk between AECs and macrophages is essential to maintain lung homeostasis [ [51] , [52] , [53] ]. Mu et al found that AECs-derived transforming growth factor-β acted on macrophages to suppress endogenous inflammatory signals during ALI [ 54 ]. Meanwhile, exosomes-derived from AECs significantly promoted the activation of macrophages, thereby exacerbating pulmonary inflammation of ALI mice [ 55 ].…”
Section: Discussionmentioning
confidence: 99%